CONTROL SYSTEM DESIGN INFORMATION IN BUDGET AND SCHEDULE PROJECT PT.XX - Adi Suryadi; Drs. H. Soetirto Sadikin, MA Drs. H. Soetirto Sadikin, MA (Jurnal Sistem Informasi, 1992)
This sat on a lot of new buildings standing that dibagun by the contracting company.Company contractor before the project activities have plans drawn up, to achieve theexpected goals. Objectives can be achieved then the control process is required, inperforming the necessary control process information quickly, accurately and timely,so that the necessary control information system project budget and schedule.